Learning Module for Electricity and Magnetism with Augmented Reality to Enhance Students' Conceptual Understanding - Abdilah, Yusup; Iswanto, Bambang Heru; Sugihartono, Iwan (WaPFi (Wahana Pendidikan Fisika), 2025)
This research aims to produce a learning module for Electricity and Magnetism with mobile augmented reality to Enhance Students' Conceptual Understanding. This research is a type of research design. The development model used is the ADDIE model, which consists of five development phases, namely analysis, design, development, implementation, and evaluation. The results of this study are learning modules that have been installed with QR-code and ModulAR apps that run on the Assmblr Edu Application. The developed materials received highly favorable ratings from experts, with content experts assigning an average score of 87% and media experts providing an average score of 86%. Teacher and student feedback indicated an average satisfaction rate of 88% and 87%, respectively. Then, the module and ModulAR apps were implemented at SMKN 1 Cikarang Pusat, which involved 36 students. The use of learning modules with mobile augmented reality based on the Inkuiri approach is also effective in enhancing students' Conceptual Understanding. It can be seen from the average n-gain score of 0.59, included in the moderate category. Furthermore, this research provides valuable insights into the potential of AR for enhancing physics education and offers practical recommendations for future research endeavors in this area.